The influence of leaf water content and isoprenoids on flammability of some Mediterranean woody species - De Lillis, Manuela; Bianco, Pietro Massimiliano; Loreto, Francesco (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2009)
The impact of water content and isoprenoids on leaf flammability was studied. Field and laboratory experiments were carried out on monoterpene-emitting evergreen broad-leaved species (Quercus ilex, Quercus suber); a needle-leaved species (Pinus halepensis) that emits and stores monoterpenes; an evergreen species (Myrtus communis) that emits isoprene but stores monoterpenes; and a deciduous species (Quercus pubescens) that emits isoprene. Photosynthesis, leaf water content (LWC) and isoprenoid emission were measured. Isoprenoid content was calculated. Temperatures of visible smoke, incandescence and flame appearance were recorded. The LWC significantly correlated with both photosynthesis and isoprenoid emissions. Linear correlation and factorial analysis revealed a positive correlation between temperature of flame appearance and LWC and a negative relationship between temperature of flame appearance and isoprenoid emission. Multiple regression analysis indicated that the temperature of flame appearance was reduced in broadleaved monoterpene-emitting species. In monoterpene emitters, the temperature of flame appearance depended for similar to 65% on LWC, whereas monoterpene emissions explained similar to 35% of the dependency. P. halepensis and M. communis, storing high levels of isoprenoids, ignited at high humidity. The results may be explained if isoprenoids indeed facilitate leaf ignition but, being dissolved in water, isoprenoids are also an indicator of a high water content that decreases flammability.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: fire; flammability phases; Monoterpenes; photosynthesis

A hypothesis on the evolution of isoprenoid emission by oaks based on the correlation between emission type and Quercus taxonomy (Oecologia, 1998)
We show that Mediterranean oaks that emit isoprene, monoterpenes or no isoprenoids belong to dierent subgenera as indicated by morpho-taxonomy and molecular genetics. On the other hand, oaks from North America and Asia that are taxonomically similar to the Mediterranean monoterpene emitter Q. ilex emit isoprene only. We surmise that isoprene emission is a genetic character which evolved ancestrally in the oak genus since this is the prevalent emission type in oaks widespread around the world and adapted to dierent environments. This ancestral character may have been either lost or modi®ed in more recent clades such as those originating the Mediterranean oaks. If our hy- pothesis is correct then the taxonomy of European oaks is validated by this independent trait. Isoprenoid emis- sion could serve as a chemo-taxonomical marker and could be used to reconstruct the phylogeny of oaks in association with molecular markers.